Revitalization of the Rau Market in Serang City as A Strategy for Local Economic Development Based on Long-Term Planning - Revaldy Putra Razwa; Satrio Ramadhan; Muhamad Fikri; Laeli Nur Khanifa (Journal of Management, Entrepreneurship, and Tourism, 2026)
This study examines the revitalization of Rau Market in Serang City as a strategy for local economic development within a long-term planning framework. The research aims to analyze the existing conditions of the market, identify structural, institutional, and spatial constraints, and formulate sustainable revitalization strategies. A qualitative descriptive approach with a single-case study design was employed. Data were collected through observations, semi-structured interviews with government officials, market managers, traders, and planning experts, as well as document analysis. The data were analyzed using thematic analysis, triangulation, and SWOT analysis. The findings indicate that Rau Market remains a strategic regional distribution center and an important source of livelihood for micro and small enterprises. However, its development is constrained by deteriorating infrastructure, inadequate sanitation and drainage systems, traffic congestion, weak institutional coordination, limited fiscal capacity, and increasing competition from modern retail and digital commerce. The study highlights that effective revitalization requires an integrated approach combining infrastructure improvement, governance reform, spatial reorganization, digital adaptation, and stakeholder participation. Integrating revitalization programs into long-term regional planning is essential for enhancing market competitiveness and supporting sustainable local economic development.